The Effect of Supervision and Work Discipline on Employee Performance at CV. Naufal Jaya Putra - Muhamad Ade Noval; M. Oktaviannur (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyse the effect of Supervision and Work Discipline on Employee Performance at CV: Naufal Jaya Putra, a company engaged in sugarcane harvesting and transportation services. The research addresses the organisation's challenges, including insufficient supervision and lack of work discipline, which affect employee productivity and efficiency. A quantitative research method was employed, with data collected from 65 respondents selected through random sampling from a population of 163 employees. Data analysis using multiple linear regression revealed that Supervision and Work Discipline significantly influence Employee Performance. These two variables explain 73.8% of the variation in Employee Performance, as indicated by an Adjusted R-squared value of 0.738. In contrast, the remaining 26.2% is influenced by unexamined factors such as motivation and work environment. The findings underscore the critical role of adequate supervision and disciplined work behaviour in enhancing employee performance and operational success. This research provides valuable insights for improving management strategies to achieve organisational outcomes.